Inhibition of Host Gene Expression by KSHV: Sabotaging mRNA Stability and Nuclear Export - Pardamean, Carissa Ikka; Wu, Ting-Ting (Frontiers in Cellular and Infection Microbiology, 2021)
Viruses are known for their ability to alter host gene expression. Kaposi sarcoma-associated herpesvirus has two proteins that obstruct host gene expression. KSHV SOX, encoded by the open reading frame 37 (ORF37), induces a widespread cytoplasmic mRNA degradation and a block on mRNA nuclear export. The other KSHV protein, encoded by the open reading frame 10 (ORF10), was recently identified to inhibit host gene expression through its direct function on the cellular mRNA export pathway. In this review, we summarize the studies on both SOX and ORF10 in efforts to elucidate their mechanisms. We also discuss how the findings based on a closely related rodent virus, murine gammaherpesvirus-68 (MHV-68), complement the KSHV findings to decipher the role of these two proteins in viral pathogenesis.